The maze runner [videorecording (DVD)] - O'Brien, Dylan, 1991-; Scodelario, Kaya, 1992-; Sangster, Thomas, 1990-; Dashner, James, 1972- (20th Century Fox Home Entertainment, 2014)
When Thomas wakes up trapped in a massive maze with a group of other boys, he has no memory of the outside world other than strange dreams about a mysterious organization known as W.C.K.D. Only by piecing together fragments of his past with clues he discovers in the maze can Thomas hope to uncover his true purpose and a way to escape.